2016
DOI: 10.1177/1534508416679402
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Analysis of the Diagnostic Evaluation of Language Variation–Screening Test: Extension to Low-Income African American Pre-Kindergarteners

Abstract: Seymour, Roeper, & deVilliers, 2003) is a culturally and linguistically unbiased screening tool used to identify children who may be at risk of significant language delays among the larger population of children who speak nonmainstream American English (NMAE) dialects. The DELV-S was developed in response to concerns about the misdiagnosis of African American and other linguistic-minority children with language disorders. In general, language assessments are particularly susceptible to performance bias, especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Within the test manual and using the high-risk category as the cut score, Seymour et al report that, in a sample of 266 5-yearolds, sensitivity was 73% and specificity was 82%. Use of the DELV-ST-II for clinical practice also has been supported by two other studies, although in both, local norms were established and recommended rather than the criterion-based scores from the test manual (Petscher, Connor, & Al Otaiba, 2012;Terry, Petscher, & Rhodes, 2016).…”
Section: Delv-st-ii Dibels and Delv-nrmentioning
confidence: 90%
“…Within the test manual and using the high-risk category as the cut score, Seymour et al report that, in a sample of 266 5-yearolds, sensitivity was 73% and specificity was 82%. Use of the DELV-ST-II for clinical practice also has been supported by two other studies, although in both, local norms were established and recommended rather than the criterion-based scores from the test manual (Petscher, Connor, & Al Otaiba, 2012;Terry, Petscher, & Rhodes, 2016).…”
Section: Delv-st-ii Dibels and Delv-nrmentioning
confidence: 90%
“…Petscher et al (2012) investigated the psychometric properties of the DELV screening test for children in kindergarten–second grade and found that when used as a screening assessment, the DELV-ST was more reliable for the assessment of language skills for students who had relatively weaker skills in comparison to those above average language skills. In a follow-up study, Terry et al (2017) extended their sample to 4-year old children and found that the same factor structure was present in the preschool sample (i.e., morphosyntactic factor and nonword repetition factor). However, only partial measurement invariance was documented which means that in comparison to the Petscher et al’s (2012) study, younger children may demonstrate different characteristics of AAVE.…”
Section: School Psychologist Assessment Practices For Readingmentioning
confidence: 97%
“…This discussion of the DELV and the DELV screening provides an example of a tool that can be used by school professionals to understand language variation in Black children. It should be acknowledged that additional research is necessary given the lack of full measurement invariance in Terry et al (2017) because one specific tool is recommended as best practices.…”
Section: School Psychologist Assessment Practices For Readingmentioning
confidence: 99%
“…Eighty-four percent of the children received either the same risk classification by both examiners or classifications differing by no more than one risk category. Finally, Petscher et al (2012) and Terry et al (2017) examined the factor structure and measurement invariance of the DELV–Screening Test Risk subtest using data from children in pre-K to second grade. These authors found support for the screener, although they recommended a two-factor structure to evaluate the grammar and nonword repetition items separately, the use of norm-referenced scores, and the development of different norms for children in pre-K as compared with K–2.…”
Section: Delv–screening Test Risk Subtestmentioning
confidence: 99%